A case of biopsy proven Acute Semyelinating Encephalomyelitis (ADEM) with Haemorrhagic Leucoencephalitis - Hashim, Hasnur Zaman; Mohamed Ibrahim, Norlinah; Wan Yahya, Nafisah; Mohd Ali, Siti Aishah; Muda, Ahmad Sobri; Mohamed Mukari, Shahizon Azura; Zaini, Izwan Zanni (Academy of Medicine, Singapore, 2011)
Dear Editor, Acute disseminated encephalomyelitis (ADEM) is an immune-mediated infl ammatory disorder of the central nervous system. It has a monophasic course which occurs after viral infection or vaccination.1,2Acute haemorrhagic leucoencephalitis (AHLE) is considered to be a hyperacute form of ADEM which is fulminant and is frequently fatal.3 There are only a few cases of biopsy-proven AHLE in the current literature. This case emphasises the importance of early recognition by magnetic resonance imaging (MRI) for institution of medical therapy.